Structure and Proportion in Hindustani Ālāp - Napier, John (Empirical Musicology Review, 2019)
In this paper, I investigate structural proportions in improvised Hindustani (North Indian) vocal music. 235 examples of two types of ālāp were examined: 175 in the genre of khayāl, 60 in the genre of dhrupad. Both studio recordings and recordings of concerts were used. Three sets of proportions were investigated: the climactic arrival at the upper tonic as a proportion of the time till a point of structural change that is made explicit through rhythmic intensification (C:R), the first point as a proportion of the whole (C:W), and point of rhythmic intensification as a proportion of the whole (R:W). Average proportions for each genre, and the degree of consistency-flexibility within each genre were measured. The results show that proportions may vary between genres, but that flexibility-consistency does not. The data obtained were also used to investigate proportions and consistency-flexibility amongst singers of similar stylistic training, across individual singers, and across different performances by the same singer. The conclusions are followed by suggestions for a further, emic-driven examination of proportionality.